The Business Judgment Rule and Shareholders Derivative Suits: A View from the Inside - Richard W. Duesenberg (Washington University Law Quarterly, 1982)
The term "business judgment rule" is one of those legal abstractions which take on fresh meaning in new and different situations. While the rule reaches back many years in American legal history, it has assumed a new role in the twilight decades of the twentieth century. These are the years that have witnessed the spate of foreign payments incidents out of which stemmed not only a series of lawsuits seeking to recover the value of such payments for corporations, but also stirrings in Congress, in regulatory bodies such as the Securities and Exchange Commission, and elsewhere. Their common focus was upon the quality of corporate governance in America. In the foreign payments lawsuits, the business judgment rule underwent an ingenious and innovative adaptation. Those corporations that had officers or directors targeted in lawsuits for return of funds allegedly wrongfully paid out established special committees drawn from the board of directors to study whether or not the best interests of the corporation mandated a stockowners' derivative action against such parties. Typically referred to as special litigation committees, they were composed of non-defendant directors who along with special counsel would study the lawsuit, examine papers, documents, and interview persons, and, after careful scrutiny, commonly conclude that the case was not in the interest of the corporation and should be dismissed. The success of this process in a number of celebrated cases moved the business judgment rule to center stage in the corporate law arena. This Article offers a defense of the rule in its more expansive application. Some may feel, as did Kierkegaard, that in defending the faith it is sometimes betrayed, but the pragmatism of this uniquely common-law creation is impressive.
Keywords: Corporations Law